Mechanical properties of oil palm empty fruit bunch impact-modified unplastices poly(vinyl chloride) composites-effect of fliter content and processing conditions - Samsudin, Sani Amril (Universiti Teknologi Malaysia, 2004)
Interest in the use of natural fibers as fillers has grown over the past few years due to the advantages it offers. The use of oil palm empty fruit bunch (EFB) as fillers in the unplasticised poly (vinyl chloride) (PVC-U) is a new attraction in the polymer composite technology. The objectives of the study is to investigate the effects of EFB fillers, screw speeds and processing temperature on processability and mechanical properties of filled and impact modified PVC-U composite extrudates. To produce the composite extrudates, the PVC resin and the additives were firstly dry blended using high speed mixer before being extruded into sheets using single screw extruder. Test specimens were prepared and shaped using cutter machine after which impact, flexural and tensile properties were determined. The results showed that only EFB-filled PVC-U composite incorporated with 10 phr of filler can be extruded with the smoother surface whereas at 20 phr the extrudates surfaces changed to be rough. The impact strength of acrylic-impact modified and EFB-filled acrylic-impact modified extrudates increased while CPE-impact modified and EFB-filled extrudates decreased as the screw speed increased. Meanwhile the flexural properties extrudates decreased as the screw speed increased. In terms of temperature effects, the maximum impact strength of impact modified occurred at temperature of 180Â°C while EFB-filled and EFB-filled acrylic-impact modified occurred at 185Â°C. The flexural modulus slightly increased while the flexural strength slightly decreased with the increase of temperature. The yield stress and yield strain of extrudates were insignificantly affected by screw speeds but slightly increased as temperature increased. The yield stress, yield strain and fusion level of extrudates increased with temperature. The overall results showed that the temperature more influence the processability and mechanical properties of both the unmodified of and impact modified extrudates compared to screw speed.